The relationship between religiosity, halal perception and intention to purchase halal food products: A comparative study between Arab Muslim and Non-Arab Muslim consumers / Azura Hanim Hashim - Azura Hanim, Hashim (2018)
This study investigates the impacts of religiosity and specific predictors that are relevant on halal food consumption. The research objectives are i) to assess the influence of religiosity and halal perception towards the intention to purchase halal food products, and ii) to develop a measurement for halal perception consisting of halal knowledge, halal consciousness, halal cautiousness, the importance of halal logo, and products that originate from Muslim countries. This study investigates the intention to purchase halal food products among Arab Muslims and non-Arab Muslims in the United Kingdom and Australia. The global Muslim population has grown rapidly in which the rate is nearly twice of the non-Muslim population in the future. Muslim population is very diverse with differences in the conformity to religious requirements and the understanding of halal food concept. There is an ample amount of literature to support the religion construct as a significant force in many individuals and the consumer behaviour. Therefore, this study provides an integrated model to comprehend the Muslims‟ attitude and behaviour using the classical theory of reasoned action (TRA) as a conceptual framework. In order to achieve the research objectives, qualitative approach (focus group discussion and interview) and quantitative approach (analysis of 788 valid questionnaires) were employed. Meanwhile, the data collection techniques used were (i) exploratory factor analysis, (ii) measurement model to test the validity assessment, and (iii) partial least square technique to examine the structural model estimation and evaluation. The results indicate a significant dissimilarity between Muslim consumers in different countries, in which this study focuses on Arab Muslim and non-Arab Muslim consumers. Religiosity gives an insightful meaning to consumer behaviour concerning halal products. This is combined with a specific set of consumer perceptions associated with food decisions. This study has developed four halal perception constructs that underwent various data purification techniques. Reliable and valid scale of halal perception allows researchers to test the relationship on a wider scope of Muslim segment and various measures to tackle and satisfy the Muslim segment. This study provides an important insight to marketing implications, as well as theoretical and methodological contributions. It also contributes to the existing body of knowledge by explaining the relationship between individual‟s religiosity and determinant factors of the intention to purchase halal food products. The findings may also serve as a guideline to formulate effective marketing strategies, locally or internationally. However, this study only focuses on Arab Muslims and non-Arab Muslims in the United Kingdom and Australia (non-Muslim countries). In short, it is recommended for future research to conduct a similar study in Muslim countries or among Muslims residing in countries other than the United Kingdom and Australia.